Analisis Kerusakan pada Bushing Apron Feeder - abraham hutabarat; Nurhabibah Paramitha Eka Utami; Diah Kusuma Pratiwi (Universitas Sriwijaya, 2021)
The mining industry, especially coal mining, has a transportation and delivery process from one location to another. In the transportation process, there are usually obstacles caused by damage to components that can hinder the delivery process. One of the transportation equipment that often fails is the Apron Feeder. The work process that works continuously and repeated loading can damage the components on the Apron Feeder, one of the components that are often damaged is the Bushing. This study aims to analyze and determine the causes of damage to the Apron Feeder Bushing. The method of this research is by looking at the microstructure of the material, the hardness value of the material, seeing surface defects using a dye penetrant. With the results obtained, namely the number of defects in the form of scratches and porosity in good Bushings which can be the cause of damage to the Bushings and on damaged Bushings, there is martensite which shows that the Bushing is deformed and brittle which results in operations which can be the cause of damage to the Bushing and the results of XRF testing ( X-Ray Fluorescence) the composition of the material on the Bushing is made of AISI 4140 where there is a difference in composition in the original specification of the material, namely SCM 415.